Safety and Efficacy of Tranexamic Acid in Aneurysmal Subarachnoid Hemorrhage: A Meta-Analysis of Randomized Controlled Trials - Ren, Junwei; Qian, Dongxi; Wu, Jiaming; Ni, Lingyan; Qian, Wei; Zhao, Guozheng; Huang, Chuanjun; Liu, Xing; Zou, Yu; Xing, Weikang (Frontiers in Neurology, 2022)
Background: In recent decades, tranexamic acid(TXA) antifibrinolytic therapy before aneurysm clipping or embolization has been widely reported, but its safety and efficacy remain controversial. This meta-analysis evaluated the efficacy and safety of TXA therapy in aneurysmal subarachnoid hemorrhage(aSAH) patients, aiming to improve the evidence-based medical knowledge of treatment options for such patients. Methods: Pubmed, Web of Science, and Cochrane Library databases were searched up to 1 March 2021 for randomized controlled trials (RCTs). We extracted safety and efficacy outcomes and performed a meta-analysis using the Review Manager software. We performed two group analyses of TXA duration and daily dose. Results: Ten RCT studies, enrolling a total of 2,810 participants(1410 with and 1400 without TXA therapy), matched the selection criteria. In the TXA duration group: TXA did not reduce overall mortality during the follow-up period(RR 1.00 [95% CI 0.81–1.22]). The overall rebleeding rate in the TXA group was 0.53 times that of the control group, which was statistically significant(RR 0.53 [95% CI 0.39–0.71]). However, an RR of 0.43 was not statistically significant in the subgroup analysis of short-term therapy(RR 0.43 [95% CI 0.13–1.39]). The overall incidence of hydrocephalus was significantly higher in the TXA group than in the control group(RR 1.13 [95% CI 1.02–1.24]). However, the trend was not statistically significant in the subgroup analysis(short-term: RR 1.10 [95% CI 0.99–1.23]; long-term: RR 1.22 [95% CI 0.99–1.50]). Treatment with TXA did not cause significant delayed cerebral ischemia(RR 1.18 [95% CI 0.89–1.56]), and its subgroup analysis showed an opposite and insignificant effect(short-term: RR 0.99 [95% CI 0.79–1.25]; long-term: RR 1.38 [95% CI 0.86–2.21]). Results in the daily dose group were consistent with those in the TXA duration group. Conclusions: Tranexamic acid does not reduce overall mortality in patients with aSAH, nor does it increase the incidence of delayed cerebral ischemia. Tranexamic acid in treating aSAH can reduce the incidence of rebleeding. However, there is no statistical significance in the ultra-early short-term and low daily dose TXA therapy, which may be due to the lack of relevant studies, and more RCT experiments are needed for further study.